2014
DOI: 10.4328/jcam.1178
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile in Thyroid Dysfunction: A Study on Patients of Bastar

Abstract: Anahtar KelimelerHipotiroidi; Hipertiroidi; Lipid Profili; Bastar'da Abstract Aim: Function of thyroid gland is regulating a wide array of metabolic activities which have direct impact on some parameters. The objective of this study was to see the effect of thyroid dysfunction on serum lipid profile parameters among the people of Bastar region. Material and Method: Blood samples were collected from 60 subjects. The blood was analyzed for the levels of thyroid stimulating hormone (TSH), tri-iodothyroinine (T3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
5
1
0
Order By: Relevance
“…This is also in agreement with the reports from earlier studies [1,[24][25][26][27]. However, contrast with the reports of Khan FA, et al [26], who reported low HDL-C with no significant changes in TC, TGs and LDL-C. The reason for these findings may be due to increased cholesteryl transfer protein mediated transfer of cholesteryl esters from HDL to VLDL and the probability of the patients being on hyperthyroidism drugs which may affect the lipid metabolism.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is also in agreement with the reports from earlier studies [1,[24][25][26][27]. However, contrast with the reports of Khan FA, et al [26], who reported low HDL-C with no significant changes in TC, TGs and LDL-C. The reason for these findings may be due to increased cholesteryl transfer protein mediated transfer of cholesteryl esters from HDL to VLDL and the probability of the patients being on hyperthyroidism drugs which may affect the lipid metabolism.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, the mean values of the TC, HDL-C and LDL-C were significantly decreased in comparison with control groups respectively, while TGs was slightly increased compared with control group. This is also in agreement with the reports from earlier studies [1,[24][25][26][27]. However, contrast with the reports of Khan FA, et al [26], who reported low HDL-C with no significant changes in TC, TGs and LDL-C.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that there was a significant increase lipid ratio of CRI-I and CRI-II, AC and AIP (p < 0.001) in patients with hypothyroidism compared to controls. Which is in accordance with study done by Khan FA et al 11 The LDL/HDL or CRI-II is a better predictor for risk of heart disease than LDL alone. The several studies have found that the LDL/HDL ratio is an outstanding monitor for effectiveness of lipid lowering therapies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies also found that there was significant positive correlation between serum TSH values and lipid parameters. 11,12 The present study found that significant positive associations between the lipid ratios (Table 4). It was stated that either the ratio of TC/HDL or LDL/HDL i.e CRI-I & II is the best lipid related predictive risk calculators of future cardiovascular events.…”
Section: Discussionsupporting
confidence: 65%
“…Our findings are in agreement with those reported by (Abo El-Maaty et al 2015;Abd-El-Rahman et al 2017) where that value of T3 was higher in 1 st trimester and gradually decreased at, 2 nd and 3 rd trimesters in pregnant she-camels. Thyroid gland plays an important role in many metabolic activities (Khan et al 2014) such as lipoprotein metabolism (Duntas 2002), and its hormonal activity has a role crucial to sustain the reproductive performance, healthy pregnancy, and brain development in fetus of animals (LaFranchi et al 2005). Reduction of thyroid hormones during pregnancy could be due to, increase their production of thyroid-binding globulin from (TBG) hepatocytes.…”
Section: Changes In Blood Biochemical Constituents and Hormonal Profiles During Pregnancy Periodmentioning
confidence: 99%